Community Perceptions of Beef Cattle Farm Sustainability in Tanjung Selamat, Medan Tuntungan, North Sumatra - Rahmadina, Rahmadina; Faisal, Agung; Putri, Annisyah Tri; Azhari, Raisa; Aprilia, Tiara; Handayani, Tri Suci (Jurnal Biologi Tropis, 2024)
This study aims to determine the community's perception of the sustainability of beef cattle farming and how obstacles are obtained in processing beef cattle waste, as well as the impact that the surrounding community feels as a result of beef cattle waste in Tanjung Selamat, Medan Tuntungan. The method of implementation of the activity uses a qualitative approach with a survey method through observation and socialization. Mеtodе obsеrvаtion of data obtained from information from local residents and direct observation independently. Respondents determined in this study were 10 respondents. In the waste indicator, the results obtained were 6 people (60%) out of 10 respondents, the hygiene indicator was 5 people (50%) out of 10 respondents, and the odor indicator was 8 people (80%) out of 10 respondents. The existence of obstacles from cattle farmers to the community due to the waste, odor, and cleanliness produced so that the odor indicator is found to have the highest level of disturbed category.